Evaluation of Serum (immunoglobulin G, M) in children with nephrotic syndrome relapse - A.Azat, Nariman F. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Nephrotic syndrome is an immune mediated disorder of the kidney associated with T cell dysfunction and secondary disturbance of B cell with changes in levels of immunoglobulin.Objectives: The objectives of this study were to compare immunoglobulin levels in children with nephrotic syndrome in relapse and healthy children, and to assess relationship between the degree of albuminuria and the mean concentrations of immunoglobulin.Methods: We studied 60 children with nephrotic syndrome during January 2008 to January 2011 in the Pediatric Nephrology consultation clinic, Children Welfare Teaching Hospital –Baghdad Medical Complex –Iraq. Urine protein and blood samples were collected from the 60 patients, and serum levels of IgG, IgM were measured. Another 20 healthy children attending the clinic were enrolled as controls.Results: In the 60 relapse cases of steroid sensitive nephrotic syndrome, compared with healthy children, the IgG level was low, IgM level was high and a highly significant relationship was found between the degree of albuminuria and the mean concentration of immunoglobulin in sera of patients (p< 0.01)Conclusion: immunoglobulin abnormalities support growing evidence that functional glomerular changes in nephrotic syndrome may result from T-cell disturbance and B-cell involvement.